1996
DOI: 10.1210/jcem.81.6.8964837
|View full text |Cite
|
Sign up to set email alerts
|

Presence of neuropeptide Y and its messenger ribonucleic acid in human islets: evidence for a possible paracrine role.

Abstract: Neuropeptide Y (NPY) has been shown to decrease insulin secretion from rodent islets. NPY messenger ribonucleic acid (mRNA) has been demonstrated in rat and mouse pancreatic islets. We, therefore, examined human islets for the presence of NPY-encoding mRNA and NPY-like immunoreactivity. Human pancreatic islets were obtained from cadaveric organ donors, using collagenase digestion and purification on BSA density gradients. Northern blot analysis, employing a human NPY riboprobe, revealed specific NPY-encoding m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
7
1
1
Order By: Relevance
“…For static incubation experiments on human islets, pancreata were removed from brain-dead heart-beating donors after informed consent was obtained from their next of kin, and islets were prepared as described previously (Leicester Royal Infirmary, Leicester, UK) (18). Islets were cultured in RPMI 1640 medium (5.5 mmol и liter Ϫ 1 glucose, 10% FCS, 100 U/ml penicillin, and 100 g/ml streptomycin).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For static incubation experiments on human islets, pancreata were removed from brain-dead heart-beating donors after informed consent was obtained from their next of kin, and islets were prepared as described previously (Leicester Royal Infirmary, Leicester, UK) (18). Islets were cultured in RPMI 1640 medium (5.5 mmol и liter Ϫ 1 glucose, 10% FCS, 100 U/ml penicillin, and 100 g/ml streptomycin).…”
Section: Methodsmentioning
confidence: 99%
“…RIN 5AH (a gift from Dr. A.E. Karlsson, Hagedorn Research Laboratory, Gentofte, Denmark; passages [14][15][16][17][18][19][20][21][22][23][24] and RIN m5F cells (a gift from Dr. S.J. Ashcroft, Physiology Department, Oxford University, UK; passages 84-100) were cultured in RPMI 1640 medium with 10% FCS (21).…”
Section: Methodsmentioning
confidence: 99%
“…Neuropeptide Y (NPY, OMIM 162640) is a 36-amino acid polypeptide that is present in the central and peripheral nervous systems, several peripheral organs, and plasma (2)(3)(4)(5). Both in vivo and in vitro studies have demonstrated that NPY inhibits glucose-stimulated insulin secretion (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that NPY mRNA is present in rat and human islets and clonal -cell lines (Jamal et al 1991, Wang et al 1994, Bennet et al 1996, Myrsen-Axcrona et al 1997. Both in vivo and in vitro studies have demonstrated that NPY inhibits glucose-stimulated insulin secretion (Petterson et al 1987, Skoglund et al 1991, probably acting via the Y1 receptor (Morgan et al 1998).…”
Section: Introductionmentioning
confidence: 96%